Governing in the Context of Uncertainty. (November 2014) - Calvert, Jane
Abstract Kaebnick, Gusmano, and Murray tackle some important issues raised by the emerging field of synthetic biology. Many of these issues arise precisely because synthetic biology is still emerging, making it hard, if not impossible, to predict how the technology will pan out. In the context of this uncertainty, Kaebnick, Gusmano, and Murray imply, we may have to change our familiar patterns of thinking and governing. It is this point that I elaborate on here. I argue that if we embrace the distinctive characteristics of emerging biotechnologies, we can shift away from attempts to analyze the risks and benefits of technological developments and toward discussions of the motivations and purposes that drive them in the first place. This perspective gives us a solid rationale for public and stakeholder engagement (or "democratic deliberation, " as Kaebnick et al. call it) and helps us address some of the concerns Kaebnick and colleagues raise about how this engagement should be organized.